Pengaruh Motivasi Belajar terhadap Hasil Belajar Pendidikan Kesetaraan Paket C - Silvia Fitri; Dea Setiajaya (Center of Education Journal (CEJou), 2021)
This study aims to analyze and test the truth of the hypothesis regarding the effect of learning motivation on learning outcomes of equivalence education package C. This research method uses a quantitative approach. Data collection techniques using a questionnaire with a Likert scale. The sample in this study was 30 residents learning package C PKBM Taruna Mandiri with data analysis techniques using simple linear regression analysis. The results showed that learning motivation had a significant effect on educationaloutcomes of equivalence package C with a sig . Value0.000 and has aninfluence of 55.8%.